Functional cellulose interfacial layer on zinc metal for enhanced reversibility in aqueous zinc ion batteries - Ho, Van-Chuong; Thi, Hai Yen Nguyen; Pham, Thi Huong; Jung, Hun-Gi; Kim, Jung Ho; Kim, Jeong F.; Mun, Junyoung (Elsevier BV, 2024)
Aqueous zinc ion batteries have emerged as promising energy storage devices due to their high safety, costeffectiveness, and environmental friendliness. However, the practical implementation of zinc ion batteries faces significant challenges associated with the poor surface stability of Zn metal anode, including dendrite growth, side reactions, and poor cycling stability. Herein, an eco-friendly cellulose layer is applied to the Zn metal anode by a scalable coating method for Zn/electrolyte interfacial engineering. The cellulose coating has multiple functions: physical passivation, reducing the resistive native oxide, enhancing wettability between the Zn metal and electrolyte, and facilitating the insertion and extraction of zinc ions during charge-discharge cycles at both room temperature and low temperature (-10 degree celsius). The cellulose-coated Zn metal anode (ZCL) also inhibits the formation of zinc dendrites, thereby reducing the risk of short circuits and capacity loss. As a result, the ZCL||ZCL symmetric cell achieved 1000 electrochemical cycles at 2 mA cm- 2, which is more than eight times longer compared to that of a bare Zn symmetric cell. The electrochemical performance of the ZCL||MnO2 full cell was also found to be superior to that using the bare Zn anode electrode.